2016
DOI: 10.1590/0100-29452016206
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Young “Dwarf Green” Coconut Plants in Soil Affected by Salts and Under Water Deficit

Abstract: -The aim was to analyze the establishment of young "Green Dwarf" coconut plants in soils affected by salts and under water stress, by evaluating leaf area, biomass production and allocation. In the experiment, conducted in protected environment in Fortaleza, CE, in statistical design of randomized blocks in a split plot arrangement, the effects of different water deficit levels (plots) were evaluated, by imposing different percentages of replacement of water losses by potential crop evapotranspiration -ETpc (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
5
0
3
Order By: Relevance
“…Plant species are often limited by multiple stress factors operating simultaneously LENSSEN et al, 2003;SILVA et al, 2016) such as soil salinity and waterlogging (GARCÍA; MENDOZA, 2014;SINGH, 2015), and plant response in these cases can be a consequence of amplified or hierarchical effects (LENSSEN et al, 2003). The results of the present work suggest that the effect of a stress factor depends on the level of the other factor to which the plant is subjected.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Plant species are often limited by multiple stress factors operating simultaneously LENSSEN et al, 2003;SILVA et al, 2016) such as soil salinity and waterlogging (GARCÍA; MENDOZA, 2014;SINGH, 2015), and plant response in these cases can be a consequence of amplified or hierarchical effects (LENSSEN et al, 2003). The results of the present work suggest that the effect of a stress factor depends on the level of the other factor to which the plant is subjected.…”
Section: Discussionmentioning
confidence: 72%
“…Silva et al (2016), studying the interactions between soil salinity and water deficit in seedlings of dwarf coconut, found that water deficit accentuated plant susceptibility to salinity. However, this interaction was evident only at low salinity levels.…”
Section: Discussionmentioning
confidence: 99%
“…A agricultura irrigada é de extrema importância para a produção agrícola, mas depende da disponibilidade ou alocação específica de recursos hídricos que, em regiões semiáridas, sofrem forte sazonalidade e risco de secas. Embora a irrigação do PIVAS seja considerada racionalizadora do uso da água na agricultura, o problema encontra-se nas fontes de água que se destinam ao perímetro, que tiveram forte déficit nos últimos anos, pondo em risco todas as plantações (LUNARDI, RABAIOLLI, 2003;SILVA et al, 2016;SILVA et al, 2017). Em julho de 2017, o açude Coremas estava com menos de 10% da capacidade e Mãe d'água com 5,6% (DNOCS, 2017).…”
Section: Condição Hídricaunclassified
“…A bananeira é muito susceptível à seca, o déficit hídrico influencia negativamente nas características do fruto (massa, comprimento, diâmetro, relação polpa/casca), e na sua resistência ao despencamento (CASTRICINI et al, 2012). Um forte fator limitante para a produção do coqueiro-anão é o estresse hídrico, o qual manifesta-se através do aborto de inflorescências e redução do número e tamanho dos frutos (LUNARDI, RABAIOLLI, 2003, SILVA et al, 2016. Temperaturas mais elevadas aumentam a evapotranspiração, demandando mais água para irrigação, situação agravada em períodos de baixas precipitações (GONDIM et al, 2011).…”
Section: Condição Hídricaunclassified
“…O manejo sob diferentes lâminas de irrigação vem sendo muito utilizado em função da otimização do consumo de recursos hídricos (SILVA et al, 2016). Desta IV INOVAGRI International Meeting, 2017 forma, o manejo eficaz da irrigação, a utilização de águas residuárias e a escolha de uma cultura de grande importância agrícola, surgem como alternativas que viabilizam a sustentabilidade agrícola de uma região.…”
Section: Introductionunclassified